The Autonomic Regulation of Tumor Growth and the Missing Links - Bautista, Maricris; Krishnan, Anand (Frontiers in Oncology, 2020)
Accumulating evidence now indicates that peripheral nerves and solid tumors mutually support the growth of each other. Tumor-derived molecular cues guide nerve infiltration to the tumor milieu, while the tumor-infiltrating nerves provide molecular support to promote tumor growth and dissemination. In this mini-review, we discuss the unique roles of sympathetic and parasympathetic nerves in promoting tumor growth and metastasis. The contribution of adrenergic and cholinergic signals, the specific receptors involved, and the downstream molecular links in both cancer cells and stromal cells are discussed for their intrinsic capacity to modulate tumor growth. We identified unappreciated niche areas in the field, an investigation of which are critical to filling the knowledge gap in understanding the biology of neuromodulation of cancers.